The Karate Kid (1984) [videorecording (DVD)] - Avildsen, John G., 1935-2017; Macchio, Ralph, 1961-; Morita, Pat, 1932-2005; Shue, Elisabeth (Columbia Pictures, 2005)
Daniel, a fatherless teenager, arrives in Los Angeles from the East and faces the difficult task of making friends. He becomes the object of bullying by a gang of karate students when he strikes up a relationship with Ali, the gang leader's ex-girlfriend. Daniel asks Miyagi, a master of martial arts, to help him learn karate. Daniel then prepares himself both mentally and physically for the fight of his life.